Talent Management Ability and Motivation on Employee Performance and Job Satisfaction as Intervening Variables of Bank Aceh Syariah Province of Aceh - A Hadi Arifin; Syaifuddin Syaifuddin; Yusuf Ronny Edward (CV. Aksara Global Akademia, 2023)
Many institutions need to pay more attention to the fact that employee abilities and motivation significantly influence the company's progress. Because of that, it is necessary to conduct research trials on whether abilities in their fields and motivation affect employee performance. Collecting data in this study used a quantitative method with a sample of 150 employees at Bank Aceh Syariah. The results of the study state that talent management is essential for companies because they work according to the desired field. Likewise, motivation also has a significant contribution to employee morale. It can be concluded that talent management and inspiration have a considerable influence on improving employee performance.